Blood rheology and proliferative retinopathy in homozygous sickle cell disease. Issue 7 (July 1986) - Serjeant, B E; Mason, K P; Acheson, R W; Maude, G H; Stuart, J; Serjeant, G R
Abstract : Some haematological and rheological features were compared in 27 age and sex matched pairs of patients (15 male, 12 female) with homozygous sickle cell (SS) disease with and without proliferative sickle retinopathy (PSR). Significant haematological differences between the groups were a higher haemoglobin and a lower fetal haemoglobin in PSR positive males and a higher MCHC in PSR positive females. The plasma viscosity and characteristics of erythrocyte filterability did not differ between those with and those without PSR, although PSR positive males had a significantly higher whole blood viscosity when measured at high shear and at the patient's own packed cell volume.